2002
DOI: 10.1016/s0925-4439(02)00158-8
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in cartilage endogenous osteogenic protein-1 (OP-1)

Abstract: Articular cartilage has a poor reparative capacity. This feature is exacerbated with aging and during degenerative joint conditions, contributing to loss of motion and impairment of quality of life. This study focused on osteogenic protein-1 (OP-1) and its ability to serve as a repair-stimulating factor in articular cartilage. The purpose of this work was to develop a quantitative method for the assessment of the content of OP-1 protein in extracts from human articular cartilage and to investigate the changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
72
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 36 publications
5
72
0
1
Order By: Relevance
“…Single-nucleotide polymorphisms (SNPs) in BMP2 were found in OA patients but their functional relevance is unknown (Valdes et al 2004(Valdes et al , 2006. The expression levels of BMP7 decline with increasing age and with progression of OA (Chubinskaya et al 2002), and the expression domains of GDF5 and GDF6 expand in adult human OA articular cartilage (Erlacher et al 1998). BMP-7 possesses cartilage-protective properties by enhancing the expression of cartilage ECM and counteracting catabolic enzyme synthesis (Huch et al 1997;Im et al 2003).…”
Section: Dysregulation Of Tgf-b or Bmp Signaling In Catabolic Bone DImentioning
confidence: 99%
“…Single-nucleotide polymorphisms (SNPs) in BMP2 were found in OA patients but their functional relevance is unknown (Valdes et al 2004(Valdes et al , 2006. The expression levels of BMP7 decline with increasing age and with progression of OA (Chubinskaya et al 2002), and the expression domains of GDF5 and GDF6 expand in adult human OA articular cartilage (Erlacher et al 1998). BMP-7 possesses cartilage-protective properties by enhancing the expression of cartilage ECM and counteracting catabolic enzyme synthesis (Huch et al 1997;Im et al 2003).…”
Section: Dysregulation Of Tgf-b or Bmp Signaling In Catabolic Bone DImentioning
confidence: 99%
“…17,18 This effect is synergistic with IGF-1, 19 and aged osteoarthritic chondrocytes still respond to BMP-7 with increased anabolic activity and viability. 12,13 Bobacz 20 and others have shown that BMP-7 improves the amount, quality, and integration of repair tissue in experimental cartilage defects. [21][22][23] Models of knee OA after mechanical injury include contusive impact applied through an arthrotomy, 24 arthroscopically, 25 or to the closed joint 26 in the rabbit, 27 dog, 26,28 sheep, 29 and horse.…”
mentioning
confidence: 97%
“…[6][7][8] Strategies that prevent cartilage degeneration in the posttraumatic knee would be very valuable. Although there is experimental evidence that this goal may be attainable, [9][10][11][12][13][14][15] recent reviews of OA treatment strategies in clinical trials concluded that definitive evidence for disease modification in OA is scant. [9][10] Prevention of OA after injury would require stimulation of repair mechanisms and promotion of an anabolic metabolism in the face of catabolic mediators such as IL-1.…”
mentioning
confidence: 99%
See 2 more Smart Citations